Adenoid cystic carcinoma of the main stem bronchus in an 11-year-old child: A case report - Beatriz Manásia Schröter; Rafael Rodrigues Torres; Roberto Augusto Plaza Teixeira; Marcela Dias Borges; Alyne Condurú dos Santos Cunha; Ana Cristina Aoun Tannuri (Journal of Pediatric Surgery Case Reports)
Introduction: Airway tumors are infrequent in children. Adenoid cystic carcinomas (ACC) are the second most common histological type. Case presentation: A previously healthy 11-year-old female presented with fever and cough for eight days. A chest x-ray revealed a large right lung opacity. Due to the opacity's extension, a contrast-enhanced chest computed tomography (CT) was done and revealed a vascularized lesion in the right main stem bronchus, with luminal narrowing and opacity suggesting pneumonia. Bronchoscopy with biopsy confirmed primary ACC. The pneumonia did not respond to ceftriaxone and was then treated with cefepime and vancomycin. The tumor was then approached via a right thoracotomy. We resected a two-centimeter segment of the right main stem bronchus and reconstructed it by an end-to-end anastomosis with a simple continuous suture on the posterior wall and simple interrupted sutures on the anterior wall. The patient left the operating room with a chest drain, having satisfactory pain control and no complications. On her sixth postoperative day on the she developed a pneumothorax due to displacement of the chest drain, which was managed by the placement of a new chest drain. On the thirteenth postoperative day she developed a pleural effusion and fever and was treated empirically with meropenem and vancomycin. The patient was discharged home with no chest drain twenty-six days after the operation. She had no further complications at the one-month follow-up. Conclusion: ACC and other airway tumors should be considered in the differential diagnosis of children with lung consolidations that do not respond to antibiotics or have atypical presentations.